Effectiveness of nutritional supplementation during the first 1000-days of life to reduce child undernutrition: A cluster randomized controlled trial in Pakistan - Sajid Bashir Soofi; Gul Nawaz Khan; Shabina Ariff; Yasir Ihtesham; Mahamadou Tanimoune; Arjumand Rizvi; Muhammad Sajid; Cecilia Garzon; Saskia de Pee; Zulfiqar A. Bhutta (Elsevier, 2022)
Summary: Background: Childhood stunting can start in the womb and continue for two years. Therefore, the first 1000 days of life between a woman's pregnancy and her child's 2nd birthday offer a unique window of opportunity to build healthier and more prosperous futures. Therefore, we aimed to assess the effectiveness of nutritional supplementation during the first 1000-days to reduce the prevalence of stunting in children at 24 months of age. Methods: In this cluster randomized controlled trial, we enrolled women during their pregnancy from two rural districts of Sindh, Pakistan. A cluster was one union council with a population of ∼25000 residents. Out of 29 clusters, we randomly allocated 6 clusters to the intervention and control groups each. Pregnant women received a monthly supply of 5 kg (i.e., 165 grams/day) of wheat soya blend plus (WSB+) during pregnancy and the first six months of their lactation period. In addition, their children received lipid-based nutrient supplement - medium-quantity (LNS-MQ) between 6-23 months of age. The primary outcome was a reduction in the prevalence of stunting in children at 24 months of age. Analysis was an intention to treat. The trial is registered on ClinicalTrial.gov, number NCT02422953. Findings: Two thousand thirty pregnant women (1017 in the intervention group and 1013 in the control group) were enrolled between August 30, 2014, and May 25, 2016. Monthly follow-ups were conducted between October 1, 2014, and October 25, 2018. At 24 months of age, we captured data from 699 (78%) of 892 live births in the intervention group and 653 (76%) of 853 live births in the control group. There was a significant difference in mean length (49.4 cm vs 48.9 cm, p =0.027), weight (3.1 kg vs 3.0 kg, p =0.013), length for age z-scores (-1.2 vs -1.5, p =0.004) and weight for age z-scores (-1.2 vs -1.5, p =0.015) among infants in the intervention compared to control group. At 24 months of age, a significant difference in the prevalence of stunting (absolute difference, 10.2%, 95% CI 18.2 to 2.3, p =0.017) and underweight (absolute difference, 13.7%, 95% CI 20.3 to 7.0, p =0.001) were observed in the intervention as compared to the control group. The prevalence of wasting was not significantly different between the intervention and control groups (absolute difference, 6.9%, 95% CI 14.1 to 0.3, p =0.057). Interpretation: Provision of WSB+ and LNS-MQ during the first 1000-days of life improved child linear growth and reduced stunting in children at 24 months. This study can be scaled-up in similar settings to lower the prevalence of stunting in children under two years of age. Funding: World Food Programme, Pakistan